Smart Cities and Environmental Sustainability: Evaluating the Nexus in South-West Nigeria - ZAKKA, Solomon Dyachia; AGBOOLA, Oluwagbemiga Paul; Olatunji, Solomon Ayodeji; YAKUBU, Sunday Ukwe-Nya (Faculty of Geography, Universitas Gadjah Mada, 2025)
Smart cities leverage advanced technologies like Internet of Things (IoT) devices, Artificial Intelligence (AI), and large-scale data analytics for gathering and interpreting data for informed decision-making and improved service delivery. This study focuses on the nexus between smart city development initiatives and environmental sustainability geared towards enhancing a better human settlement in the South-west region, of Nigeria. One of the objectives is to identify and evaluate the factors contributing to the development of smart city initiatives and to evaluate their contributions towards environmental sustainability. An empirical Quantitative approach method comprising Questionnaires was used. A total of three hundred (300) sample Questionnaires were administered and two hundred and eighty-six (286) questionnaires were retrieved and used for analysis. The distribution of Questionnaires cut across professional experts within the built environment and relevant stakeholders. Analysis was done, using the regression technique of the Statistical Package for the Social Sciences (SPSS) software, Version 22. Some of the results included the following: smart economic factors such as Entrepreneurship and Innovation (B = 0.899, sig. = 0.001) Productivity, (B = 0.794, sig. = 0.001) Local and global interconnectivity (B = 0.713, sig. = 0.001). Similarly, the smart mobility factors, have mixed and modal access (B = 0.632, sig. = 0.001); Prioritized clean and non-motorized options (B = 0.604, sig. = 0.001); Integrated ICT (B = 0.656, sig. = 0.001). Generally, the study revealed that smart economy, smart mobility, and smart environment have the most influence on the achievement of environmental sustainability in South-west, Nigeria.Received: 2024-01-23 Revised: 2024-08-02 Accepted: 2025-01-24 Published: 2025-02-12